ANALISIS SEQUENTIAL EXPLANATORY HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AQIDAH AKHLAK DITINJAU DARI DISIPLIN, MINAT BELAJAR, DAN KECERDASAN EMOSIONAL - Isomudin Isomudin (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2019)
The objectives of the research is to investigate learning outcomes correlation to variables learning discipline, interest to learn, and emotional intelligence, either individually or together. The study was conducted on 282 learning outcomes in multi stage random sampling from 951 Senior High School students throughout the City of Cilegon. The research used a combination mixsed method of quantitative and qualitative research with sequential explanatory design. Analysis using simple partial regression and correlation, multiple correlation. The result of study indicated that usion of this is that there is very a significant and positive relationship between independent variables means learning discipline, interest to learn, and emotional intelligence together with performance dependent variable learning outcomes, calculation result of coefficient correlation is ry.123 = 0,2 and coefficient determinant is r2y.123 =0,027, and contribute to learning outcomes is 2,65 %, there are other influential factors is 97,35 % to learning outcomes. While the relationship independently of independent variables, learning discipline has no relationship and is non significant with learning outcome compared with other variables of correlation coefficient is ry.1 = 0,004 and coefficient determinant is r2y.1=0,000014 contribution to learning outcomes is 0,0014 %, interest to learn, correlation coefficient is ry.2= 0,14 very low, the nature of the spirit of learning with an interesting impression, fun, grow innovative and new ways of solving a problem of learning tasks, the results of qualitative research support quantitative research, Emotional intelligence,, correlation coefficient is ry.3= 0,082 coefficient determinant is r2y.3=0,007 contribute to learning outcomes is 0,67 %, while is 99,33 % contributed by other variables that are related to learning outcomes, the qualitatively advantages of good ability, the nature that reflects the feeling of optimism, able to do new things, have broad insight, full responsibility, persistent, high enthusiasm in learning.